Preparation and evaluation of Vinpocetine self-emulsifying pH gradient release pellets - Mengqi Liu; Shiming Zhang; Shuxia Cui; Fen Chen; Lianqun Jia; Shu Wang; Xiumei Gai; Pingfei Li; Feifei Yang; Weisan Pan; Xinggang Yang (Taylor & Francis Group, 2017)
The main objective of this study was to develop a pH gradient release pellet with self-emulsifying drug delivery system (SEDDS), which could not only improve the oral bioavailability of Vinpocetine (VIN), a poor soluble drug, but reduce the fluctuation of plasma concentration. First, the liquid VIN SEDDS formulation was prepared. Then the self-emulsifying pH gradient release pellets were prepared by extrusion spheronization technique, and formulation consisted by the liquid SEDDS, absorbent (colloidal silicon dioxide), penetration enhancer (sodium chloride), microcrystalline cellulose, ethyl alcohol, and three coating materials (HPMC, Eudragit L30D55, Eudragit FS30D) were eventually selected. Three kinds of coated pellets were mixed in capsules with the mass ratio of 1:1:1. The release curves of capsules were investigated in vitro under the simulated gastrointestinal conditions. In addition, the oral bioavailability and pharmacokinetics of VIN self-emulsifying pH gradient release pellets, commercial tablets and liquid VIN SEDDS were evaluated in Beagle dogs. The oral bioavailability of self-emulsifying pH gradient release pellets was about 149.8% of commercial VIN tablets, and it was about 86% of liquid VIN SEDDS, but there were no significant difference between liquid SEDDS and self-emulsifying pH gradient release pellets. In conclusion, the self-emulsifying pH gradient release pellets could significantly enhance the absorption of VIN and effectively achieve a pH gradient release. And the self-emulsifying pH gradient release pellet was a promising method to improve bioavailability of insoluble drugs.